Decreased Serum Sirtuin-1 in COPD - Yanagisawa, S; Papaioannou, AI; Papaporfyriou, A; Baker, JR; Vuppusetty, C; Loukides, S; Barnes, PJ; Ito, K (Elsevier, 2017)
Background The protein deacetylase sirtuin-1 (SIRT1) is an antiaging molecule that is decreased in the lung in patients with COPD. Recently, SIRT1 was reported to be detectable in serum, but serum SIRT1 (s120S) levels have not yet been reported in patients with COPD. Methods Serum SIRT1 protein of all samples was measured by Western blot, and the SIRT1 protein band densities were calculated and compared with clinical parameters. Results Several molecular sizes of SIRT1, including 120 kDa (actual size) and fragments (102 and 75 kDa) were quantified by Western blot. Among them, only the 120-kDa s120S was significantly decreased in patients with COPD compared with the control subjects without COPD (s120S ratio in healthy subjects = 0.90 ± 0.34 vs those with COPD = 0.68 ± .24; P = .014) and was positively correlated with airway obstruction (FEV1/FVC, r = 0.31; P = .020); its severity measured by FEV1 % predicted (r = 0.29; P = .029). s120S also showed a positive correlation with BMI (r = 0.36; P = .0077) and diffusing capacity of the lung per unit volume (the carbon monoxide transfer coefficient: KCO%) (r = 0.32; P = .025). It was also significantly decreased with increasing severity of lung emphysema (r = –0.40; P = .027) and with a clinical history of frequent COPD exacerbations (infrequent vs frequent, 0.76 ± 0.20 vs 0.56 ± 0.26; P = .027). SIRT1 was not detected in supernatant of A549 and primary epithelial cells in normal culture conditions. Conclusions s120S was decreased in the patients with COPD, potentially as reflected by the reduced SIRT1 within cells as a result of oxidative stress, and might be a potential biomarker for certain disease characteristics of COPD